2003
DOI: 10.1002/mats.200350030
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Charged Poly(propylene imine) Dendrimers: Theoretical Investigation

Abstract: A mean‐field model for charged dendrimers has been elaborated and applied to Astramol dendrimers of 5th generation in salt‐free solution. The free energy of a dendrimer molecule was minimized with respect to the dendrimer size and to the profile of counterion distribution. The model of highly stretched freely jointed chain was used to describe the elasticity of long branches, the dissociated groups were assumed to be localized mostly on the periphery of the molecule, and the electrostatic interactions were des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
25
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 24 publications
(35 reference statements)
5
25
0
Order By: Relevance
“…This result is consistent with the predictions of the scaling in the quasi-neutral regime (Eq. (19)). As the charge fraction is increased, the size behavior of the dendrimer is seen to approach the high salt osmotic regime scaling (Eq.…”
Section: Scaling Behavior Of Ae Qe and Qi Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…This result is consistent with the predictions of the scaling in the quasi-neutral regime (Eq. (19)). As the charge fraction is increased, the size behavior of the dendrimer is seen to approach the high salt osmotic regime scaling (Eq.…”
Section: Scaling Behavior Of Ae Qe and Qi Modelsmentioning
confidence: 99%
“…Adding charged groups to dendrimers was proposed as a way to achieve open core conformations desired for drug delivery applications. Such considerations have motivated a number of theoretical [17][18][19][20][21][22][23][24][25][26][27][28][29] and experimental [30][31][32][33][34] studies of charged dendrimer molecules. For instance, Welch and Muthukumar 17 used Monte Carlo simulations to show that the size and conformations of dendrimers with charged branch and terminal points are strongly dependent on the salt concentration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some examples of their use include lithographic materials, nanoscale catalysts, drug delivery systems, rheology modifiers, bioadhesives, and magnetic resonance imaging (MRI) contrast agents [3]. Though experimental studies [4][5][6][7][8][9], theory and simulations [10][11][12][13][14] have already brought about some insight into the way charged dendrimers react to various conditions, the research on them is far from being completed. For instance, the number of simulation papers is still very limited and some predictions reported in them contrast with experimental results.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the molecular volume of dendrimers also depends on terminal groups which prevent the core of dendrimers from other molecules. 14 Recently, experimental, 15,16 analytical, 17 and computational [18][19][20][21][22][23][24][25] studies of these novel macromolecules have focused on charged dendrimers. Welch and Muthukumar studied first the charged dendrimers by using Monte Carlo simulations with implicit conversions, and they found that the ion strength of solution is an important parameter for controlling the behavior of charged dendrimers.…”
Section: Introductionmentioning
confidence: 99%